2012
DOI: 10.1890/11-0893.1
|View full text |Cite
|
Sign up to set email alerts
|

Prey–predator dynamics in rotifers: density‐dependent consequences of spatial heterogeneity due to surface attachment

Abstract: Abstract. Classical models of prey-predator interactions assume that per capita prey consumption is dependent on prey density alone and that prey consumption (functional response) and consumer proliferation (numerical response) operate on the same timescales and without time lags. Several modifications have been proposed for resolving this timescale discrepancy, including variants where the functional response depends on both prey and predator densities. A microcosm system with the rotifer Brachionus 'Nevada' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…For the experiments reported here, these rotifers were fed batch-cultured Chlamydomonas reinhardtii until used in treatments. Although some species of Brachionus tend to attach to surfaces as animal density increases, which creates conditions for consumer-dependent feeding (Vadstein et al 2012), we only very rarely observed this behavior in our study, and Fussmann et al (2005) only found a consumer-dependent effect on feeding rate at unnaturally high rotifer densities.…”
Section: Methodscontrasting
confidence: 66%
“…For the experiments reported here, these rotifers were fed batch-cultured Chlamydomonas reinhardtii until used in treatments. Although some species of Brachionus tend to attach to surfaces as animal density increases, which creates conditions for consumer-dependent feeding (Vadstein et al 2012), we only very rarely observed this behavior in our study, and Fussmann et al (2005) only found a consumer-dependent effect on feeding rate at unnaturally high rotifer densities.…”
Section: Methodscontrasting
confidence: 66%
“…The most common rotifer species observed in this study, such as Keratella quadrata, K. cochlearis, K. tecta, Polyarthra dolichoptera, P. vulgaris, and Trichocerca similis, are cosmopolitan (Segers, 2007). However, species such as Filinia longiseta and Lepadella patella, which are also known to be also cosmopolites, were observed only at one station, which might be a result of unfavorable environmental conditions and/or overpredation by fish larvae and aquatic invertebrates in these water bodies (Murtaugh, 1989;Vadstein et al, 2012). The most common Cladocera species was Bosmina longirostris, which is a well-known indicator of eutrophication (Jaramillo and Pinto, 2010).…”
Section: Discussionmentioning
confidence: 60%
“…A5). Additionally, lower dilution increases the importance of recycled nutrients relative to fresh supply (Vadstein et al ). This impedes the competitive ability of a low‐quality species of which a higher portion is recycled by grazing (Fig.…”
Section: Discussionmentioning
confidence: 99%